PENENTUAN DIAMETER PIPA OPTIMAL DALAM PERENCANAAN SISTEM PENYEDIAAN AIR BERSIH DI KECAMATAN WONOTIRTO KABUPATEN BLITAR PROVINSI JAWA TIMUR - Nenny Roostriawaty; Sriliani; Erfan, Muhammad (Institut Teknologi Nasional Malang, 2021)
Optimization of pipe diameter in the planning of clean water supply systems in Wonotirto District aims to determine the projected demand for clean water in Wonotirto District until 2028. This research was conducted because currently the distribution of clean water in the study location is still not completely fulfilled. Topographical conditions, most of which are in mountainous areas, cause one of the reasons for the difficulty of distributing clean water. The pipe diameter optimization planning in this study uses the Hazen-William method. The data used are the population in the last 10 years, geoelectric data, and topographic maps of Wonotirto District, Blitar Regency. Based on the results of the planning, it is found that the projected number of population in 2020 is 37,013 people. the discharge of clean water needs is 63.73 liters / second, the dimensions of reservoir 1 are planned to be 6 m x 4 m x 3 m, reservoir 2 is planned to be 6.5 m x 4 m x 3 m. The type of pipe used is the type of PVC with a diameter of 0.75 inches, 1 inch, 1.25 inches, 1.5 inches, 2 inches, 2.5 inches, 3 inches, 4 inches, 6 inches, where planning calculations are carried out using the Hazen-William Method. The limited amount of groundwater discharge at the location means that not all villages in the Wonotirto District area have their clean water needs met and it is hoped that further research will improve this research.